Antiretroviral Treatment for HIV in Rural Uganda: Two Year Treatment Outcomes of a Prospective Health Centre/Community-Based and Hospital-Based Cohort - Kipp, Walter; Konde-Lule, Joseph; Saunders, L. Duncan; Alibhai, Arif; Houston, Stan; Rubaale, Tom; Senthilselvan, Ambikaipakan; Okech-Ojony, Joa (PloS one, 2012)
In sub-Saharan Africa, a shortage of trained health professionals and limited geographical access to health facilities present major barriers to the expansion of antiretroviral therapy (ART). We tested the utility of a health centre (HC)/community-based approach in the provision of ART to persons living with HIV in a rural area in western Uganda.
Keywords: Antiretroviral Treatment; HIV; Outcomes